2014
DOI: 10.1002/lt.24014
|View full text |Cite
|
Sign up to set email alerts
|

Association between anesthesiologist experience and mortality after orthotopic liver transplantation

Abstract: The anesthesiologist has been recognized as an integral member of the liver transplant team, and previous studies have demonstrated that inter-anesthesiologist variability can be a driver of outcomes for high-risk patients. We hypothesized that anesthesiologist experience, defined as the number of previous liver transplants performed at our institution, the Icahn School of Medicine at Mount Sinai, would be independently associated with outcomes for liver transplant patients. Eight hundred forty-nine liver tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
0
32
1
2
Order By: Relevance
“…The overall postoperative mortality rate was 20%; previous studies showed a distribution from 10% to 20% [30,31] . As expected, the mortality rate was much higher in patients with PRCs than in those without PRCs.…”
Section: Discussionmentioning
confidence: 98%
“…The overall postoperative mortality rate was 20%; previous studies showed a distribution from 10% to 20% [30,31] . As expected, the mortality rate was much higher in patients with PRCs than in those without PRCs.…”
Section: Discussionmentioning
confidence: 98%
“…Our center also has a dedicated liver anesthesia team for all transplant cases. There is significant literature that shows that having a dedicated LT anesthesia team influences the number of blood transfusions, number of laboratory tests performed, length of postoperative ventilation, length of ICU stay, and the rate of postoperative complications as well as mortality . Whether or not there is an association between DCD outcomes and dedicated LT anesthesia teams needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesiologists have a measurable effect on transplant outcome and on the use of costly resources . Yet, there are few rules or policies to assure transplant centers and their patients that anesthesiologists are adequately prepared and available to provide care.…”
Section: Discussionmentioning
confidence: 99%
“…The issue was brought to the attention of the Society for the Advancement of Transplant Anesthesia (SATA), a US and Canadian organization whose mission includes principles of action that serve the best interests of transplant patients and organ donors . The importance of this issue was highlighted by the well‐documented association between LTAT organization, recipient mortality, and the cost of care incurred by the use of high‐intensity resources . In response, SATA appointed a task force to determine what actions were needed to support uninterrupted expert care at all liver transplant centers.…”
mentioning
confidence: 99%